2015
DOI: 10.1155/2015/319312
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis Leading to Severe Dilated Cardiomyopathy in a Patient with Dengue Fever

Abstract: Background. Majority of dengue fever cases follow a benign self-limiting course but recently rare presentations and complications are increasingly seen due to rising burden of disease. Cardiac involvement in dengue fever with fatal outcome is a very rare complication. We report a case of 44-year-old patient who presented with symptoms of severe acute congestive heart secondary to myocarditis induced cardiomyopathy caused by dengue virus infection. Case Presentation. A 44-year-old man presented to ER with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 9 publications
1
15
1
1
Order By: Relevance
“…1 Except for genetic factors, recently, myocarditis (ecology virus infection or autoimmune inflammation) caused by DCM has attracted much attention. 2,3 Myocarditis is a myocardial inflammatory disease and it is characterized by the degeneration, necrosis, and apoptosis of cardiomyocytes which also demonstrates inflammatory cell infiltration and myocardial interstitial remodeling. The activation of nuclear factor (NF)-κB signaling and the production of inflammatory cytokines (such as tumor necrosis factor [TNF]-α; IL-6, IL-1, IL-2, IL-4, and IL-10; monocyte chemoattractant protein [MCP]-1; interferon [IFN]-γ, etc) are the main factors for myocarditis.…”
Section: Introductionmentioning
confidence: 99%
“…1 Except for genetic factors, recently, myocarditis (ecology virus infection or autoimmune inflammation) caused by DCM has attracted much attention. 2,3 Myocarditis is a myocardial inflammatory disease and it is characterized by the degeneration, necrosis, and apoptosis of cardiomyocytes which also demonstrates inflammatory cell infiltration and myocardial interstitial remodeling. The activation of nuclear factor (NF)-κB signaling and the production of inflammatory cytokines (such as tumor necrosis factor [TNF]-α; IL-6, IL-1, IL-2, IL-4, and IL-10; monocyte chemoattractant protein [MCP]-1; interferon [IFN]-γ, etc) are the main factors for myocarditis.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study carried out in China during an outbreak has shown that the prognosis of dengue patients with or without myocarditis did not differ [26]. However, there have been several case reports which have reported fatal outcomes in patients with dengue myocarditis [24,[27][28][29][30][31]. A significant positive association between myocarditis and the severity of dengue has been shown in one study [26].…”
Section: Myocarditis/pericarditismentioning
confidence: 95%
“…Summary of studies providing data on atypical manifestations of dengue. Sheetal et al[8], Neeraja et al[25], Li et al[26], Miranda et al[32] Nigam et al[9],Navinan et al[10], Virk et al[11], Dhariwal et al[12] 15% Khongphatthanayothin et al[5], Kirawittaya et al[20], Yacoub et al[21], Wali et al[22], Neeraja et al[25], Li et al[26] Miranda et al[24], Marques et al[27], Tahir et al[28], Sane et al[29],Ku et al …”
mentioning
confidence: 99%
“…La posibilidad de miocardiopatía dilatada inducida por DENV debe siempre tenerse en cuenta si un paciente tiene DENV y choque refractario, asociado a signos y síntomas de insuficiencia cardíaca congestiva. Se debe enfatizar de nuevo en que la detección temprana, la reanimación in-mediata, la clasificación del paciente, evitando la sobrecarga con líquidos intravenosos, son medidas cruciales para salvar vidas y puede mejorar la supervivencia de los pacientes [51]. Debe generarse conciencia, sospecha y atención de apoyo en la consecución de resultados positivos y benignos en estos pacientes [44].…”
Section: Universidad De Manizales -Facultad De Ciencias De La Saludunclassified